The Novel Secreted Meloidogyne incognita Effector MiISE6 Targets the Host Nucleus and Facilitates Parasitism in Arabidopsis - Shi, Qianqian; Mao, Zhenchuan; Zhang, Xiaoping; Ling, Jian; Lin, Runmao; Zhang, Xi; Liu, Rui; Wang, Yunsheng; Yang, Yuhong; Cheng, Xinyue; Xie, Bingyan (Frontiers in Plant Science, 2018)
Meloidogyne incognita is highly specialized parasite that interacts with host plants using a range of strategies. The effectors are synthesized in the esophageal glands and secreted into plant cells through a needle-like stylet during parasitism. In this study, based on RNA-seq and bioinformatics analysis, we predicted 110 putative Meloidogyne incognita effectors that contain nuclear localization signals (NLSs). Combining the Burkholderia glumae–pEDV based screening system with subcellular localization, from 20 randomly selected NLS effector candidates, we identified an effector MiISE6 that can effectively suppress B. glumae-induced cell death in Nicotiana benthamiana, targets to the nuclei of plant cells, and is highly expressed in early parasitic J2 stage. Sequence analysis showed that MiISE6 is a 157-amino acid peptide, with an OGFr_N domain and two NLS motifs. Hybridization in situ verified that MiISE6 is expressed in the subventral esophageal glands. Yeast invertase secretion assay validated the function of the signal peptide harbored in MiISE6. Transgenic Arabidopsis thaliana plants expressing MiISE6 become more susceptible to M. incognita. Inversely, the host-derived RNAi of MiISE6 of the nematode can decrease its parasitism on host. Based on transcriptome analysis of the MiISE6 transgenic Arabidopsis samples and the wild-type samples, we obtained 895 differentially expressed genes (DEGs). Integrating Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, we found that expression of MiISE6 in Arabidopsis can suppress jasmonate signaling pathway. In addition, the expression of genes related to cell wall modification and the ubiquitination proteasome pathway also have detectable changes in the transgenic plants. Results from the present study suggest that MiISE6 is involved in interaction between nematode-plant, and plays an important role during the early stages of parasitism by interfering multiple signaling pathways of plant. Moreover, we found homologs of MiISE6 in other sedentary nematodes, Meloidogyne hapla and Globodera pallida. Our experimental results provide evidence to decipher the molecular mechanisms underlying the manipulation of host immune defense responses by plant parasitic nematodes, and transcriptome data also provide useful information for further study nematode-plant interactions.